Presentation - Sánchez-Mesa, Domingo; Sánchez Montes, María José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Hybridizations and Transmediality between Fictional and Documentary Genres: Images and Critique of Post-Truth